Compiling longjiang opera vocal music guidebook for teaching students in harbin normal university，harbin,heilongjiang province, China - Xue, Wang; Yodwised , Chutasiri; Gatemean, Kampanat (Journal of Roi Kaensarn Academi, 2024)
The purpose of this study are:(1) To study and collect the vocal music of the Longjiang opera.(2) To create guidebook for Longjiang opera.(3)To applying guidebook to teaching experimental group .(4) To evaluate the effectiveness of the teaching. This study adopts a mixed research method, combining qualitative research with quantitative research. In the research stage, interview method and observation method are used. The researchers observed the learning status of third-year students majoring in vocal music at Harbin Normal University. In the development stage, quantitative methods are adopted through experimental design and statistical description of the conclusions. Twenty third-year students of vocal music major in Harbin Normal University were selected as experimental subjects to carry out the teaching experiment of "Longjiang opera singing". The singing effect of Longjiang opera was analyzed through formative test and summative test. Based on the basic principles and theoretical knowledge of Longjiang opera, combined with the author's research and expert interviews, this paper has developed a guidebook for vocal music majors aiming at the weaknesses of Longjiang opera after exploring and researching the existing academic materials. The guidebook course plan of Longjiang opera has been developed, which consists of four parts: "Theoretical knowledge of Longjiang opera", "Singing of Longjiang opera tunes", "Summary review" and "Summative test". This guidebook is finally determined through interviews with experts, aiming to explore how to teach and sing Longjiang opera, so as to play a role in protecting and developing the local music culture of Heilongjiang Province.